Knowledge, Attitude and Practice of Patients Visiting Dental Department of Hetauda Hospital Towards Orthodontic Treatment - Chaudhary, Nabin Kumar; Shah, Ranjana; Sapkota, Anisha; Nepali, Padam; Chaudhary, Suvin (Journal of College of Medical Sciences-Nepal, 2024)
Background There are insufficient studies to assess knowledge, attitude, and practice (KAP) towards orthodontic treatment in general patients visiting dental treatment in government hospitals, although the studies have been done in high school students and orthodontic patients. The objective of this study was to assess the KAP of patients towards orthodontic treatment. Methods In this cross-sectional study, data from 400 patients visiting dental department of Hetauda Hospital were collected. The data was collected through the structured questionnaire. A 3-point Likert scale was used to assess the degree of KAP of patients towards orthodontic treatment. Descriptive statistics including frequency, percentage, and mean for Likert scale were calculated. Results All the patients had a good degree of knowledge except heredity and habits such as thumb sucking, tongue thrusting, and mouth breathing influence the occurrence of malalignment of teeth (moderate degree of knowledge). Also, all the patients had a good degree of attitude and practice towards orthodontic treatment. Conclusions The data was encouraging as the patients had a good degree of KAP towards orthodontic treatment.